Profitability and Market Competitiveness of the Electric Vehicles Geely Auto - Shang, Minghao; Baldo, Nova C. (International Journal of Global Economics and Management, 2025)
This study investigates the factors influencing the profitability and market competitiveness of Geely Auto within the electric vehicle sector. Using a qualitative research design, data were gathered through interviews with ten industry professionals, including managers, analysts, and supply chain experts familiar with Geely’s strategic operations. Thematic analysis of the interview responses revealed five factors shaping Geely’s competitive positioning: aggressive pricing strategies, supply chain integration and partnerships, innovation in smart technologies and green initiatives, market adaptation and customer engagement, and financial monitoring with strategic investment. The findings suggest that Geely’s success in the evolving electric vehicle market is driven by its ability to integrate cost-effective strategies with technological innovation and market responsiveness. The study concludes that a multi-faceted strategic approach, emphasizing both operational efficiency and market-driven decision-making, is essential for maintaining profitability and competitive advantage in the dynamic global EV industry.